A quest for excitation: Theoretical arguments and immunohistochemical evidence of excitatory granular cells in the ELL of Gnathonemus petersii. Issue 3 (October 2016) - Hollmann, V.; Engelmann, J.; Gómez-Sena, L.
Highlights: A physiologically and anatomically plausible model of the electrosensory lobe is presented. Transition from time to rate encoding is achieved through corollary discharge based sensory gating. Sensory input and corollary discharge interactions regulate the balance of excitation and inhibition in the efferent cells. An all inhibitory network is predicted to be less capable of sensory recoding. In accordance with model prediction, neuroanatomical evidence of excitatory granular cells is presented. Abstract: The Electrosensory Lateral Line lobe (ELL) is the first central target where the electrosensory information encoded in the spatiotemporal pattern electroreceptor afferent discharges is processed. These afferents encode the minute amplitude changes of the basal electric field through both a change in latency and discharge rate. In the ELL the time and rate-coded input pattern of the sensory periphery goes through the granular cell layer before reaching the main efferent cells of the network: large fusiform (LF) and large ganglion (LG) cells. The evidence until now shows that granular cells are inhibitory. Given that large fusiform cells are excited by the sensory input, it remains a mystery how the afferent input produce excitation through a layer composed by only inhibitory cells. We addressed this problem by modeling how the known circuitry of the ELL could produce excitation in LF cells with only inhibitory granular cells. Alternatively we show that a network composed of a mix of excitatory and inhibitory granular cell not only performs better, as expected, carrying excitation to LF cells but it does so robustly and at higher sensitivity by enhancing the contrast of the electric image between the periphery and the ELLs output. We then show with refined histological methods that a subpopulation of the granular cells indeed are excitatory, providing the necessary input for this contrast enhancing mechanism.